Patients' perceptions of safety in emergency medical services: an interview study. Issue 10 (21st October 2020) - Venesoja, Anu; Castrén, Maaret; Tella, Susanna; Lindström, Veronica
Abstract : Background: Research on patient safety in emergency medical services (EMS) has mainly focused on the organisation's and/or the EMS personnel's perspective. Little is known about how patients perceive safety in EMS. This study aims to describe the patients' experiences of their sense of safety in EMS. Methods: A qualitative design with individual interviews of EMS patients (n=21) and an inductive qualitative content analysis were used. Results: Patients' experiences of EMS personnel's ability or inability to show or use their medical, technical and driving skills affected the patients' sense of safety. When they perceived a lack of professionalism and knowledge among EMS personnel, they felt unsafe. Patients highlighted equality in the encounter, the quality of the information given by EMS personnel and the opportunity to participate in their care as important factors creating a sense of safety during the EMS encounter. Altogether, patients' perceptions of safety in EMS were connected to their confidence in the EMS personnel. Conclusions: Overall, patients felt safe during their EMS encounter, but the EMS personnel's professional competence alone is not enough for them to feel safe. Lack of communication or professionalism may compromise their sense of safety. Further work is needed to explore how patients' perceptions of safety can be used in improving safety in EMS.